2015
DOI: 10.1007/s00403-015-1553-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine, asymmetric dimethyl arginine (ADMA) and other arginine–NO pathway metabolite levels in patients with psoriasis

Abstract: Hyperhomocysteinemia, a well-known and independent risk factor for cardiovascular disease, has been related in several studies with psoriasis patients. It has been suggested that homocysteine leads to endothelial dysfunction by causing an accumulation of asymmetrical dimethyl arginine (ADMA), a potent endogenous nitric oxide (NO) synthase inhibitor of the L-arginine-NO pathway. However, limited data is available regarding the psoriasis and ADMA relationship. In this study, we aimed to investigate the serum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 28 publications
4
44
4
1
Order By: Relevance
“…Our findings are in keeping with a recent study on 42 patients with chronic plaque psoriasis in which PASI score strongly correlated with the ADMA level . This study along with our present data highlight the potential role of ADMA in the pathogenesis of psoriasis.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in keeping with a recent study on 42 patients with chronic plaque psoriasis in which PASI score strongly correlated with the ADMA level . This study along with our present data highlight the potential role of ADMA in the pathogenesis of psoriasis.…”
Section: Discussionsupporting
confidence: 93%
“…However, unlike these results, patients with psoriasis were found to have high blood homocysteine in other five studies again in our country and five in Italy and one each in Ireland and Norway [20][21][22][23][24][25][26][27][28][29][30][31] . In the literature, studies showing psoriasis being accompanied by high blood homocysteine seem to be predominant (Table 3).…”
contrasting
confidence: 77%
“…After the studies made in 1990s where high levels of homocysteine were found in plasma samples of subjects who had or would likely to have a history of myocardial infarction, ischemic stroke or peripheral vascular disease and the association of homocysteine with atherosclerosis and hypercoagulability had been shown [6][7][8][9][10][11][12] , along with increased attention to the comorbidities of psoriasis, as far as we know, 19 studies have been conducted to explore homocysteine levels in these patients. Homocysteine level was found to be high in 12 and normal in 7 of these studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Since this sulfur-containing amino acid is not taken through diet and not producing protein, homocysteine is formed via methionine catabolism 8,11,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic profiling of unconventional specimens obtained in a noninvasive manner is particularly challenging (sampling, sample storage, sample treatment, chemical analysis, and data processing) and has not been extensively addressed. Thus, it is not surprising that more attention has been paid to the alterations in the blood metabolite composition in psoriasis (7,8), and studies focused on the skin are rare (6,9,10).…”
Section: © 2016 American Association For Clinical Chemistrymentioning
confidence: 99%